The effect of dry-land training on functional strength and swimming performance of 10-12 years old swimmers - Ozeker, Kutlukhan Yagmur; Bilge, Murat; Yildirim Kose, Damla Selin (Progress in Nutrition, 2020)
The objective of this study was to examine the effect of three weeks of dry-land training on functional strength and swimming performance in addition to eight weeks of swimming training of 15 female athletes in the 10-12 years age group with at least three years of training history. A total of 30 athletes between the ages of 10-12 participated in the study; it was divided into control and experimental groups. Methods: Muscle strength tests and swimming performance tests were applied to all groups before and after the test at eight week intervals. The dry-land training program applied to the experimental group was prepared for the 10 most frequently used muscle groups in swimming branch in the literature. Descriptive statistics were applied to the obtained data. The normality of data were analyzed with Kolmogorov-Smirnov test and it was found that the data showed a normal distribution. Paired samples t test was used for within group comparisons in the analysis of data and independent samples t test was used for comparison of measurement times of the groups. Results: Trapezius middle left-right deltoid anterior left-right, deltoid middle-right, triceps brachii left-right, gluteus maximus left-right, tensor facia latasol-right, biceps femoris left-right, quadriceps femoris left-right; a statistically significant difference was found between the groups in terms of 400 m free style and 50 m free style critical swimming speed variability. When the pre-test and post-test values of the experimental group were compared, Trapezius middle left, deltoid anterior left-right, biceps brachii left-right, brachio radialis left-right, gluteus maximus left-right, tensor fasia lata left-right, biceps femoris left-right, quadriceps femoris left-right statistically significant differences were found in 400 m free style, 50 m free style critical swimming speed variables (p <0.01). Conclusion: Dry-land training has a positive effect on swimming and functional strength performance in 10-12 years old strength swimmers.